As relações entre a escola e o mundo do trabalho na educação de jovens e adultos trabalhadores um estudo com professores de EJA do ensino medio - Luft, Hedi Maria (Universidade do Vale do Rio do Sinos, 2010)
The study focus the relations between school and the world of work in the workers adults and young adults education, an action research was taken, along with the Public Junior School (state supported), in Santa Rosa – RS. On the action perspective, the study was aimed to develop the continued graduation of teachers who work with students who are not in school age, qualifying them with services to develop educational practices with more consequences in the education of the junior high school workers. On the research perspective the study focused on: What function and goals do the teachers attribute to the political-pedagogical approach used on the young adults teaching? What is your work conception and how the is the teaching approached by the teachers? What are the contributions of different areas related to the work dimension? Theoretical, what knowledge are legitimized on that space? How does the teacher link the scientific-techinical knowledge with the student workers knowledge? To reach the proposed goal
Relations between school and the world of work in adult workers adults and young adults education: a study with EJA teacher in high school education
Keywords: escola; formação docente; saberes; trabalho; educação de jovens e adultos; knowledge; school; teacher formation; work; young adults and adults education; Ciências Humanas